2020
DOI: 10.1159/000507549
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Reliability, and Agreement of Transperineal Ultrasound Measurement: Results from a Longitudinal Cohort Study

Abstract: <b><i>Objectives:</i></b> To evaluate the feasibility, reliability, and agreement of serial transperineal ultrasound (TPU) assessment of fetal head station (parasagittal angle of progression [psAOP], head-perineum distance [HPD], and head-symphysis distance [HSD]) and sonographic cervical dilatation (SCD), compared to fetal head station and cervical dilatation determined by vaginal examination, respectively. <b><i>Methods:</i></b> This was a prospective longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…61,65,66 Angle of progression (Figure 5) is the angle between the sagittal midline of the symphysis pubis and line dropping from the lowermost point of the symphysis pubis tangentially to the deepest point of the fetal head, on transperineal ultrasound. 67 The automated assessment of AoP, now available in some ultrasound systems, measures the AoP in a parasagittal plane and was demonstrated to be feasible, correlate well with assessment of fetal station by vaginal examination 68 and in excellent agreement with the originally described midsagittal AoP 69 .…”
Section: Assessment Of Fetal Head Position and Stationmentioning
confidence: 61%
“…61,65,66 Angle of progression (Figure 5) is the angle between the sagittal midline of the symphysis pubis and line dropping from the lowermost point of the symphysis pubis tangentially to the deepest point of the fetal head, on transperineal ultrasound. 67 The automated assessment of AoP, now available in some ultrasound systems, measures the AoP in a parasagittal plane and was demonstrated to be feasible, correlate well with assessment of fetal station by vaginal examination 68 and in excellent agreement with the originally described midsagittal AoP 69 .…”
Section: Assessment Of Fetal Head Position and Stationmentioning
confidence: 61%
“…Benediktsdottir et al reported ultrasound to be unable to measure CD > 8 cm [34]. Kwan et al reported overall good agreement of DE and TPU measurements for CD while also stating that the ability of TPU to measure CD decreased with growing CD [35]. This suggests that TPU is more suitable for the latent stage than for the later stages of labour.…”
Section: Discussionmentioning
confidence: 99%
“…More and more information about the use of ultrasound for the assessment of labor progress has been accumulated in recent years, and it has become a relatively new way of assessing childbirth [37]. Transperineal ultrasound parameters (HPD and AOP) significantly correlated with each other as well as with both labor progress and mode of birth [38][39][40][41][42][43]. Chan and Ng [41] suggested that a combination of AOP and HPD can increase their predictive potential of normal vaginal birth and sensitivity to 97.7%.…”
Section: Discussionmentioning
confidence: 99%